Surgical treatment of peripheral ulcerative keratitis and necrotizing scleritis in granulomatosis with polyangiitis - Lu, Cheng-Wei (Saudi Med J, 2016)
The efficacy of surgical management of refractory ophthalmic complications of granulomatosis with polyangiitis (GPA), which is a sight threatening was reported. A 70-year-old man presented with a progressively worsening pain and redness in his right eye during the previous 6 months, and decreasing visual acuity that started one month earlier. He was misdiagnosed and treated as keratitis elsewhere, but the pain has not decreased. The diagnosis of necrotizing scleritis with peripheral ulcerative keratitis (PUK) in GPA was made in our department. Surgery was performed with necrotic tissue removal, combined with cryotherapy and a conjunctival flap covering surgery. The symptom was relieved after surgery, and the patient’s ocular condition remained stable thereafter. This case first demonstrates limited ophthalmic GPA (such as, PUK and necrotizing scleritis) that was not sensitive or aggravated for traditional methods can be successfully treated by combined surgical interventions.